2014
DOI: 10.1007/s00455-013-9510-9
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Dysphagia in Myotonic Dystrophy Type 1: A Systematic Review

Abstract: A systematic review was conducted to investigate the pathophysiology of and diagnostic procedures for oropharyngeal dysphagia in myotonic dystrophy (MD). The electronic databases Embase, PubMed, and The Cochrane Library were used. The search was limited to English, Dutch, French, German, Spanish, and Portuguese publications. Sixteen studies met the inclusion criteria. Two independent reviewers assessed the methodological quality of the included articles. Swallowing assessment tools, the corresponding protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…For example silent aspiration, a severe swallowing abnormality, can occur without subjectively suffering from it . Moreover, several patient groups (neurodegeneration, stroke, head and neck oncology postradiation and postsurgery) tend to have sensory deficits that may contribute to inaccurate judgment . Inaccuracy of perceptual judgment (underestimation of the problem) may manifest itself in fewer subjective complaints .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example silent aspiration, a severe swallowing abnormality, can occur without subjectively suffering from it . Moreover, several patient groups (neurodegeneration, stroke, head and neck oncology postradiation and postsurgery) tend to have sensory deficits that may contribute to inaccurate judgment . Inaccuracy of perceptual judgment (underestimation of the problem) may manifest itself in fewer subjective complaints .…”
Section: Discussionmentioning
confidence: 99%
“…One hundred seven patients with OD complaints were recruited at the outpatient clinic for otorhinolaryngology and divided into three main diagnostic groups (Table I). Fifty-four patients suffered from neurological diseases (e.g., Parkinson's disease, stroke), 35 patients from miscellaneous or other etiologies (e.g., Zenker's diverticulum, cervical spine degeneration), and 18 patients from head and neck oncological diseases. At the time of examination, all head and neck oncological patients had received curative oncological treatment at least 6 months prior to inclusion.…”
Section: Participantsmentioning
confidence: 99%
“…Swallowing function was assessed in patients with DM1 and presymptomatic DM1 mutation carriers by using FEES, clinical and molecular analyses, and the Dysphagia Handicap Index (DHI) . To evaluate swallowing physiology, FEES was performed with food and liquids at different standardized consistencies . We chose FEES analysis for this study because it is an inexpensive, easy‐to‐perform, well‐tolerated, and sensitive technique that allows anatomic and functional evaluation of the pharyngolaryngeal phase of swallowing .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that gastrointestinal alterations are common in myotonic dystrophy type 1 (DM1) . Dysphagia, which is defined as difficulty in swallowing food and/or liquids, has a prevalence ranging from 25% to 80% in DM1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation